A BRIEF STUDY OF AGNI ASSESSMENT SCALE - Basumatary, Khagen; Bhatta, *Chumi (International Journal of Ayurveda and Pharma Research, 2019)
The primary aim and objective of Ayurveda is to maintain the health of healthy person and to eradicate the diseases of a diseased person is the secondary one. One whose Dosa, Agni, Dhatu and Malas are in balanced state and whose senses, mind and soul are functioning properly is a healthy individual. Agni maintains the physiology of this Dehadesha. In other words Agni controls the state of biological equilibrium of Dosha, Dhatu and Mala. The derangement of Agni produces various diseases and it is the root cause of all diseases. In Ayurveda the term Agni is used in the sense of digestion of food and metabolic products. Agni converts food in the form of energy, which is responsible for all the vital functions of our body and it is necessary to develop a scale to measure the Agni level of human beings.